2013
DOI: 10.1186/2008-2231-21-15
|View full text |Cite
|
Sign up to set email alerts
|

5,6-Dimethoxybenzofuran-3-one derivatives: a novel series of dual Acetylcholinesterase/Butyrylcholinesterase inhibitors bearing benzyl pyridinium moiety

Abstract: BackgroundSeveral studies have been focused on design and synthesis of multi-target anti Alzheimer compounds. Utilizing of the dual Acetylcholinesterase/Butyrylcholinesterase inhibitors has gained more interest to treat the Alzheimer’s disease. As a part of a research program to find a novel drug for treating Alzheimer disease, we have previously reported 6-alkoxybenzofuranone derivatives as potent acetylcholinesterase inhibitors. In continuation of our work, we would like to report the synthesis of 5,6-dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Structurally, SJ-172550 is characterized by having α,β-unsaturated carbonyl system attached to the 2-(2-chloro-6-ethoxyphenoxy)acetic acid methyl ester. Accordingly, in continuation of our research program to find novel anti-cancer agents [12-16] and considering the diverse biological activities of rigid chalcones [17], we have synthesized a series of 3-benzylidene-4-chromanones bearing 2-(2-chloro-6-alkoxyphenoxy) acetic acid esters. The related analogs of 3-benzylidene-4-chromanones were also prepared for more studying of structure-activity relationships (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, SJ-172550 is characterized by having α,β-unsaturated carbonyl system attached to the 2-(2-chloro-6-ethoxyphenoxy)acetic acid methyl ester. Accordingly, in continuation of our research program to find novel anti-cancer agents [12-16] and considering the diverse biological activities of rigid chalcones [17], we have synthesized a series of 3-benzylidene-4-chromanones bearing 2-(2-chloro-6-alkoxyphenoxy) acetic acid esters. The related analogs of 3-benzylidene-4-chromanones were also prepared for more studying of structure-activity relationships (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an electron‐donating methoxy group at the para position of the phenyl ring reduced the inhibition potential against the AChE enzyme. According to literature, substitution of electron‐withdrawing groups, such as halogens, on the phenyl ring make the compounds more active than the unsubstituted compound while substitution of electron‐donating groups, such as methyl groups, on the phenyl ring make the compounds less active (Nadri et al, ; Yoon et al, ). However, our observations have shown that the methoxy substituted compound 7g is more potent than its unsubstituted compound 7a (IC 50 = 29.9 ± 3.1 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The benzylidene-substituted DHEA derivatives 1a-m were synthesized through the aldol condensation [36] of DHEA with corresponding benzaldehyde derivatives (Figure 2). …”
Section: Resultsmentioning
confidence: 99%